Rational engineering of Geobacter sulfurreducens electron transfer components: a foundation for building improved Geobacter-based bioelectrochemical technologies - Dantas, Joana M.; Morgado, Leonor; Aklujkar, Muktak; Bruix, Marta; Londer, Yuri Y.; Schiffer, Marianne; Pokkuluri, P. Raj; Salgueiro, Carlos (Frontiers in Microbiology, 2015)
Multiheme cytochromes have been implicated in Geobacter sulfurreducens (Gs) extracellular electron transfer (EET). These proteins are potential targets to improve EET and enhance bioremediation and electrical current production by Gs. However, the functional characterization of multiheme cytochromes is particularly complex due to the co-existence of several microstates in solution, connecting the fully reduced and fully oxidized states. Over the last decade, new strategies have been developed to characterize multiheme redox proteins functionally and structurally. These strategies were used to reveal the functional mechanism of Gs multiheme cytochromes and also to identify key residues in these proteins for EET. In previous studies, we set the foundations for enhancement of the EET abilities of Gs by characterizing a family of five triheme cytochromes (PpcA-E). These periplasmic cytochromes are implicated in electron transfer between the oxidative reactions of metabolism in the cytoplasm and the reduction of extracellular terminal electron acceptors at the cell’s outer surface. The results obtained suggested that PpcA can couple e-/H+ transfer, a property that might contribute to the proton electrochemical gradient across the cytoplasmic membrane for metabolic energy production. The structural and functional properties of PpcA were characterized in detail and used for rational design of a family of 23 single site PpcA mutants. In this review, we summarize the functional characterization of the native and mutant proteins. Mutants that retain the mechanistic features of PpcA and adopt preferential e-/H+ transfer pathways at lower reduction potential values compared to the wild-type protein were selected for in vivo studies as the best candidates to increase the electron transfer rate of Gs. For the first time Gs strains have been manipulated by the introduction of mutant forms of essential proteins with the aim to develop and improve bioelectrochemical technologies.